STUDENTS' DIFFICULTIES IN LEARNING THE CONCEPT OF CURVED-SIDED SPACES: A LITERATURE REVIEW - Aprilia, Renisa Dwi; Haninah, Salwa; Salmaa, Yusriyyah Mardhiyyah; Arifin, Fatkhul (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study aims to identify and review several articles discussing students' learning difficulties in understanding material related to curved-sided geometric shapes in elementary schools. The research method employed is a literature study, in which data is collected from various scientific journals relevant to students' learning difficulties in comprehending curved-sided spaces. The findings indicate that students face multiple challenges, including difficulties in understanding basic concepts, remembering formulas, and applying appropriate problem-solving strategies. Common errors include procedural mistakes, difficulties in transforming information, and improper use of mathematical symbols. Factors contributing to these difficulties include a lack of interest in mathematics, the abstract nature of mathematical concepts, and insufficient practice in applying the concepts learned. This research is expected to serve as a recommendation for teachers and education practitioners to improve teaching methods and provide more intensive exercises to help students better understand the concepts related to curved-sided spaces.